Molecular Genetic Alterations in Renal Cell Carcinomas With Tubulocystic Pattern: Tubulocystic Renal Cell Carcinoma, Tubulocystic Renal Cell Carcinoma With Heterogenous Component and Familial Leiomyomatosis-associated Renal Cell Carcinoma. Clinicopathologic and Molecular Genetic Analysis of 15 Cases. Issue 7 (August 2016) - Ulamec, Monika; Skenderi, Faruk; Zhou, Ming; Krušlin, Božo; Martínek, Petr; Grossmann, Petr; Peckova, Kvetoslava; Alvarado-Cabrero, Isabel; Kalusova, Kristyna; Kokoskova, Bohuslava; Rotterova, Pavla; Hora, Milan; et al.
Abstract : The characteristic morphologic spectrum of tubulocystic renal cell carcinoma (TC-RCC) may include areas resembling papillary RCC (PRCC). Our study includes 15 RCCs with tubulocystic pattern: 6 TC-RCCs, 1 RCC-high grade with tubulocystic architecture, 5 TC-RCCs with foci of PRCC, 2 with high-grade RCC (HGRCC) not otherwise specified, and 1 with a clear cell papillary RCC/renal angiomyoadenomatous tumor-like component. We analyzed aberrations of chromosomes 7, 17, and Y; mutations of VHL and FH genes; and loss of heterozygosity at chromosome 3p. Genetic analysis was performed separately in areas of classic TC-RCC and in those with other histologic patterns. The TC-RCC component demonstrated disomy of chromosome 7 in 9/15 cases, polysomy of chromosome 17 in 7/15 cases, and loss of Y in 1 case. In the PRCC component, 2/3 analyzable cases showed disomy of chromosome 7 and polysomy of chromosome 17 with normal Y. One case with focal HGRCC exhibited only disomy 7, whereas the case with clear cell papillary RCC/renal angiomyoadenomatous tumor-like pattern showed polysomies of 7 and 17, mutation of VHL, and loss of heterozygosity 3p. FH gene mutation was identified in a single case with an aggressive clinical course and predominant TC-RCC pattern. The following conclusions were drawn: (1) TC-RCC demonstrates variable status of chromosomes 7, 17, and Y even in cases with typical/uniform morphology. (2) The biological nature of PRCC/HGRCC-like areas within TC-RCC remains unclear. Our data suggest that heterogenous TC-RCCs may be associated with an adverse clinical outcome. (3) Hereditary leiomyomatosis-associated RCC can be morphologically indistinguishable from "high-grade" TC-RCC; therefore, in TC-RCC with high-grade features FH gene status should be tested.